E-learning frameworks: a survey - Queirós, Ricardo (2014)
In recent years the concept of eLearning Framework emerged associated with several initiatives promoted by educational organizations. These initiatives share a common goal: to create flexible learning environments by integrating heterogeneous systems already available in many educational institutions. The paper provides an introductory survey on eLearning Frameworks. It gathers information on these initiatives categorizes them and compares their features regarding a set of predefined criteria such as: architecture, business model, primary user groups, technical implementations, adopted standards, maturity and future development.